PROTOTYPE OF MOBILE EDUCATION TECHNOLOGY WITH MULTIMEDIA FOR AUTISTS CARE PROGRAM - Samosir, Ridha Sefina; Syahrani, Erwin; Lumba, Ester; Kusumawati, Dyah (LPPM Nusa Mandiri, 2021)
Autism is a neurobiological development disorder in children. This disorder causes difficulties for children to communicate and establish relationships with the environment. The impact, they cannot properly interact with other people or their surroundings, because of their inability to understand what other people mean. Parents or families who have family members with autism need the convenience and wide openness of information regarding education paths, pathways of care and treatment, lines of work, pathways of therapy, and other path information. Includes information about autism such as symptoms, characteristics of autism, and how to deal with tantrums. All information needed by all these parties should be easily accessible. This study proposes an educational technology that contains information needed by patients and their families. This educational technology is mobile-based and equipped with multimedia features so that educational materials are easier to understand. The method used for system development is prototyping. The output of this research is a prototype design of mobile-based educational technology with additional multimedia features.